Emma and Phebe: "Weavers of the Border" - Salesa, Damon (Waka Kuaka, 2014)
Emma Coe (1850-1913) and Phebe Coe (1863-1944) were sisters born in Samoa to an American father and a Samoan mother. Raised in Samoa, the sisters went on to live much of their lives in Melanesia, mostly in northern New Guinea. The sisters became prominent in business, planting, colonial society, ethnographic work and public culture. This essay is a biography of the sisters, whose histories were extraordinary, as they made public and commercial lives at a time when few women did or indeed could, and where a mixed-race identity was often made into a burden.